Psychological Factor: A Predictor of Consumer Buying Behaviour in Retail Outlets in South-West Nigeria - Olodo, Hameedat Bukola; Balogun, Alherillahi Yusuf (NIU Journal of Social Sciences, 2025)
Retailers operating in both informal and formal retail environments often face challenges in meeting customer expectations and increasing profitability due to limited insight into the diverse psychological factors that influence consumer purchasing behaviour. This study investigated the impact of selected psychological variables on consumer buying behaviour in retail outlets across South-West Nigeria. The target population comprised customers from both informal and formal retail settings within the region. Primary data was collected through a survey of 1,000 respondents, with selection of 500 each from Lagos and Oyo States using a convenience sampling method to select participants from designated markets. To analyse the data, regression analysis and analysis of variance (ANOVA) were employed to determine the comparative influence of psychological variables. The results indicated that perception and learning significantly and positively affect consumer buying behaviour in both retail types at the 0.05 level of significance. Additionally, motivation was found to have a positive and significant influence in formal retail outlets, though it showed no significant effect in informal settings. Meanwhile, beliefs and attitudes were not statistically significant in shaping consumer buying decisions in either outlet type. The study concludes that psychological factors play a vital role in influencing consumer purchasing decisions in both retail formats, as evidenced by F-statistics of 69.675 and 12.680, with p-values of .000 in both cases. Based on these findings, it is recommended that retailers develop a marketing tactics effective and suitable to motivate at the same time influence consumers’ buying behavior, targeting the factors that determines their purchase decisions to include past experience, product awareness, social status, personal values, and emotional responses. Keywords: Consumer Behaviour, Psychological Factors, Retail Outlets, Perception, Learning, Motivation, South-West Nigeria.